Biological activities of wheat middlings bioprocessed with Bacillus spp. (April 2017) - Reque, Priscilla Magro; Orlandini Werner, Júlia Antônia; Barreto Pinilla, Cristian Mauricio; Folmer Corrêa, Ana Paula; Rodrigues, Eliseu; Brandelli, Adriano
Abstract: Wheat middlings were cultivated with five different Bacillus spp. strains in order to evaluate their effect on the phenolic composition and bioactive properties of this agro-industrial waste. Total phenolic content and phenolic profile as well as antioxidant, antibacterial, antihypertensive and prebiotic activities were determined. The bioprocessed wheat middlings exhibited an increase in antioxidant capacity (ABTS and DPPH assays) and total phenolic compounds. Changes in the phenolic profile, with identification of some hydroxybenzoic and hydroxycinnamic acids were also observed by HPLC-DAD analysis. Selected samples inhibited the growth of Gram-positive ( L. monocytogenes and B. cereus ) and Gram-negative ( E. coli ) bacteria. The sample cultured for 72 h with B. subtilis FTC01 also promoted the growth of a probiotic strain ( Lactobacillus acidophilus ) and showed a high angiotensin-I converting enzyme-inhibitory activity. Thus, the use of bioprocessing techniques can be an interesting approach to improve the bioavailability of compounds with health-promoting properties from wheat coproducts. Highlights: Wheat middlings were bioprocessed with different Bacillus spp. Bioprocessed samples showed increased antioxidant activity and phenolic content. Treatment with Bacillus increased prebiotic potential of wheat middlings. Inhibition of angiotensin I-converting enzyme was also observed.